Cytidine deaminase Apobec3a induction in fallopian epithelium after exposure to follicular fluid - Brachova, Pavla (Gynecol Oncol, 2017)
OBJECTIVE: Ovarian carcinomas that originate from fallopian epithelial cells are suggested to arise due to repeated exposure to ovulatory follicular fluid (FF). Mechanistic explanation(s) for how this occurs are unknown. Here, we sought to understand if FF exposure to fallopian epithelial cells could induce DNA damage and expression of a known family of DNA mutators, apolipoprotein B mRNA editing enzyme, catalytic polypeptide (APOBEC) cytidine deaminases. METHODS: Follicular fluid and matched patient plasma samples were obtained from donors. Fallopian epithelial cells (FT33-TAg, FT189, FT190, and FT194) were cultured with FF or plasma for 24 hr, and cell proliferation and DNA damage were assessed. Effects of FF on Apobec gene expression was determined by qRT-PCR and western blot analyses. Fallopian epithelial cells were transfected with an APOBEC3A expression vector and DNA damage was assessed. RESULTS: Follicular fluid exposure increased epithelial cell proliferation as measured by three independent methods, and DNA damage accumulation as assessed using three independent measures. This effect was specific to FF, as matched patient plasma did not have the same effects. Increased expression of Apobec3a was observed in fallopian epithelial cells following exposure to 5 of 8 patient FF samples, and transient overexpression of APOBEC3A was sufficient to induce double strand DNA breaks. CONCLUSIONS: Follicular fluid can induce cell proliferation and DNA damage accumulation in cultured fallopian epithelial cells. Increased expression of APOBEC3A, a known DNA mutator, may explain the high incidence of DNA damage after FF exposure. The role of Apobec3a in ovulation-induced inflammation warrants further investigation.